2021
DOI: 10.3390/s21237874
|View full text |Cite
|
Sign up to set email alerts
|

Field-Effect Sensors Using Biomaterials for Chemical Sensing

Abstract: After millions of years of evolution, biological chemical sensing systems (i.e., olfactory and taste systems) have become very powerful natural systems which show extreme high performances in detecting and discriminating various chemical substances. Creating field-effect sensors using biomaterials that are able to detect specific target chemical substances with high sensitivity would have broad applications in many areas, ranging from biomedicine and environments to the food industry, but this has proved extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Covalent bonding ofers stronger interactions than physical adsorption because it can ofer an exceptionally thin, uniform, and stable surface. Chemical conjugation via the coupling of carboxylic acid group (COOH), amino group (NH 2 ), alcohol group (OH), or azide-alkyne cycloaddition, and sulfhydryl-maleimide coupling are usually used to covalently attach hydrophilic functional groups to the surface of the nanomaterial [35]. Accordingly, most chemical covalent modifcations in electrochemical dehydrogenase biosensor studies were formed using an amide bond between amine-modifed oligonucleotides and the carboxylic acid groups of the nanotube [12,20,21].…”
Section: Covalent Bondingmentioning
confidence: 99%
“…Covalent bonding ofers stronger interactions than physical adsorption because it can ofer an exceptionally thin, uniform, and stable surface. Chemical conjugation via the coupling of carboxylic acid group (COOH), amino group (NH 2 ), alcohol group (OH), or azide-alkyne cycloaddition, and sulfhydryl-maleimide coupling are usually used to covalently attach hydrophilic functional groups to the surface of the nanomaterial [35]. Accordingly, most chemical covalent modifcations in electrochemical dehydrogenase biosensor studies were formed using an amide bond between amine-modifed oligonucleotides and the carboxylic acid groups of the nanotube [12,20,21].…”
Section: Covalent Bondingmentioning
confidence: 99%
“…Therefore, the best immobilization method should be selected according to the characteristics of the biomimetic element to develop a B‐EN with good performance. [ 43 ] Since the concept of B‐EN was proposed, various subject groups around the world have started to study B‐ENs, as shown in Table 1 . The Park group's research is more extensive and contains various biomimetic components as well as sensors and attempts to combine microfluidic systems with EN.…”
Section: Development Of Bioelectronic Nosementioning
confidence: 99%
“…Tai Hyun Prak FET-type B-EN [44] Application of nanomaterials in B-EN [45] Microfluidic system combined with B-EN [46] Tomasz Wasilewski Peptide-based B-EN [ 26b,47] Ping Wang B-EN is based on cells and OSNs [48] Research on in vivo B-EN [49] Jadranka Travas-Sejdic Insect odor receptor-based biosensor [ 32,39,50] Yanxia Hou SPR-type B-EN [ 38,51] Corrado Di Natale Various types of biosensors [52] ement to develop a B-EN with good performance. [43] Since the concept of B-EN was proposed, various subject groups around the world have started to study B-ENs, as shown in Table 1. The Park group's research is more extensive and contains various biomimetic components as well as sensors and attempts to combine microfluidic systems with EN.…”
Section: Groups Research Contentmentioning
confidence: 99%
“…As an environmentally friendly material, biomaterials have good application prospects and can be used in the fields of environment, energy and sensing. 99,100 Saithongdee et al 101 prepared a nanofibrous membrane sensor from a curcumin-doped zein solution by electrospinning and amidation cross-linking under the conditions of citric acid and heating. The sensor is able to achieve a colorimetric response to iron ions with a color change from yellow to brown with an optical detection limit of 0.4 mg L −1 (Fig.…”
Section: Electrospun Nanofiber Fluorescent Sensor For Detection Of Ha...mentioning
confidence: 99%